THE INFLUENCE OF JOB STRESS TO JOB SATISFACTION AMONG EMPLOYEES IN IEC MALAKA MEDAN - Albert Albert; Mega Sanjaya; Kuandi Chandra; Bestadrian Prawiro Theng; Benny Lim (Bajang Institute, 2022)
Job satisfaction is a very important factor to get the optimal work. When a sense of satisfaction in the work of course, it will try as much as possible with all the ability to finish the work. Thus, productivity of employee work will increase optimally. To maintain employees’ job satisfaction in the workplace so that future employees the work can manage stress well and can provide a positive impact to the employees (increased job satisfaction, productivity, and performance of employees) and enterprise (low levels of employee absenteeism, employee turnover, and so on). The purposes of this research are to know there is influence of job stress towards job satisfaction at IEC Malaka Medan. Research methods which used are descriptive statistic analysis coefficient correlation and coefficient of determinant, simple linear regression analysis and Z test. The result of this research is job stress has influence toward job satisfaction in IEC Malaka Branch. There is strong negative relationship between job stress managed by employee with job satisfaction in IEC Malaka Branch. Most of employees in IEC Malaka Branch are disagree in job satisfaction and moderate in job stress at this company. If the employees satisfy from what they have received from the company, then that employee will give more than what is expected by company, and they will continue to improve its performance. With employee satisfaction and avoiding the job stress, the employee productivity will increase. Hence, job satisfaction has significance benefit both for the employees and the company, especially as it creates a positive situation in the company’s work environment.